THE INFLUENCE OF MEDIA LEARNING SIGUM IN THE PANDEMIC TIME COVID-19 - Salamudin Salamudin; Anda Kelana; Muslim Muslim; Nirwan Nirwan; Zuhud Suriono (AT-TAJDID, 2021)
Covid-19 has been declared a pandemic since the beginning of 2020 causing the learning process to be carried out from home with an online system at all levels of education. This study aims to determine how much influence the GIS Learning Media will have during the Pandemic. This type of research is a qualitative research based on literature study. This research was conducted at SMK Negeri 2 Binjai. The results showed that: (1) Students already have basic facilities that are used to carry out online learning with GIS learning media; (2) online learning with SIGUM learning media is very flexible in its implementation and is able to encourage independent learning and motivation to be more active in participating in learning; and (3) Learning using SIGUM learning media is included in innovative learning, which of course has weaknesses and strengths. In essence, innovative learning requires teacher creativity in designing, arranging and conditioning students so that they are enthusiastic in learning, have the ability to think, solve problems faced correctly, especially problems related to everyday life and the world of work later.Keywords: Learning Media, SIGUM, Pandemic Covid-19